IMPLEMENTASI KEBIJAKAN PROGRAM PENDIDIKAN KECAKAPAN KERJA (PKK) DI KABUPATEN PANDEGLANG - Ajat Suhrajat (LPPM STIA Banten, 2022)
This study discusses the Implementation of the Work Skills Education Program (PKK) Policy in Pandeglang Regency. The aim of the research is to find out the implementation efforts made by the Ministry of Education, Research and Culture Technology through the Directorate of Courses and Training, Directorate General of Vocational Education, to Non-formal Institutions in Pandeglang Regency. This study uses a descriptive qualitative approach. Determination of informants using techniques purposive sampling. Data collection techniques through observation, direct interviews and documentation. Testing the validity of the data uses triangulation of data sources and member checks which are associated with the theory of public policy implementation by Van Metter & Van Horn, Deddy Mulyadi (2016). Data analysis techniques using Miles and Hubberman. The results of the research show that the implementation of the Work Skills Education Program (PKK) Policy in Pandeglang Regency is still not optimal.The implementation carried out by non-formal institutions is still general in nature and is more oriented towards government work routines. This condition hinders the implementation process for people who do not yet have skills in terms of work. The researcher recommends that non-formal institutions and the Education and Culture Office of Pandeglang Regency provide ongoing motivational assistance and support to people who need expertise. In the future, it is expected that the open unemployment rate in Pandeglang Regency can be reduced significantly.